Bridging Technology and Education: Understanding EdTech in Today;s World & Internship Experience at Hubblehox Technologies - Tougani, Riyank (ATLAS SkillTech University, 2025)
This study offers a comprehensive examination of the dynamic relationship between technology and education. It delves into the fundamental aspects of EdTech, defining its scope and highlighting its critical role in modern education. The study explores how technological advancements are transforming educational practices underscoring its potential to revolutionize learning experiences. The project traces the historical evolution of educational technology, from the pre-digital era through significant milestones such as the computer age, internet revolution, and the rise of AI and personalized learning. It provides a detailed analysis of the global EdTech market, including market size, growth projections, regional dynamics, and key drivers and challenges. The study also reviews various business models and revenue streams within the EdTech industry. A significant portion of the project is dedicated to exploring key technologies driving innovation in EdTech, including artificial intelligence, virtual and augmented reality, blockchain, the Internet of Things, and more.
Project Report on Bridging Technology and Education: Understanding EdTech in Today;s World & Internship Experience at Hubblehox Technologies (2023-2025) Under the Guidance of Prof. Cleston D'Costa
Keywords: dynamic relationship; technology; EdTech; artificial intelligence; augmented reality; virtual reality; blockchain; Internet of Things